Macroscopical contact pressure and microscopic leakage performance analysis of rubber seal considering thermal oxygen aging effect. (December 2022) - Sun, Heng-Chao; Hao, Yan-Yan; Wang, Li-Na
Leakage performance of rubber seal is a key factor of spacecraft system, which is required long life. But the degradation law of the rubber seal performance in long service period is limited to qualitative analysis for its macro contact performance, and the quantitative research of rubber seal leakage performance is rarely involved considering thermal oxygen aging effect. Therefore, the thermal oxygen aging mathematical model is firstly established to predict the life of rubber material by aging tests. Secondly, the finite element model (FEM) of rubber seal performance analysis considering thermal oxygen aging effect is built to obtain the degradation law of its macroscopic contact performance with the increase of service time. Thirdly, the micro-leakage model of rubber seal considering thermal oxygen aging effect is established based on the material surface microstructure, contact pressure, and contact width, and the leakage rate of rubber seal is calculated by the model. Finally, the micro-leakage model of rubber seal is modified based on the experimental results, so the calculation accuracy of leakage rate is improved.